Plasma homocysteine levels and risk of congestive heart failure or cardiomyopathy: A Mendelian randomization study - Wang, Xinyi; Chen, Zhuo; Tian, Wende; Zhang, Jie; Li, Qiuyi; Ju, Jianqing; Xu, Hao; Chen, Keji (Frontiers in Cardiovascular Medicine, 2023)
Background Although observational studies have demonstrated associations between elevated plasma homocysteine levels and the risk of cardiovascular diseases, controversy remains. Objective This study investigated the causal association of plasma homocysteine levels with congestive heart failure and cardiomyopathy risk. Methods We performed a two-sample Mendelian randomization (MR) study of congestive heart failure (n = 218,792), cardiomyopathy (n = 159,811), and non-ischemic cardiomyopathy (n = 187,152). Genetic summary data on the association of single-nucleotide polymorphisms with homocysteine were extracted from the most extensive genome-wide association study of 44,147 individuals. MR analyses, including the random-effect inverse variance-weighted (IVW) meta-analysis, weighted median, simple median, maximum likelihood, penalized weighted median, MR-PRESSO, and MR-Egger regression, were used to estimate the associations between the selected single-nucleotide polymorphisms and congestive heart failure or cardiomyopathy. Results The MR analyses revealed no causal role of higher genetically predicted plasma homocysteine levels with congestive heart failure risk (random-effect IVW, odds ratio [OR] per standard deviation (SD) increase in homocysteine levels = 1.753, 95% confidence interval [CI] = 0.674–4.562, P = 0.250), cardiomyopathy (random-effect IVW, OR per SD increase in homocysteine levels = 0.805, 95% CI = 0.583 to 1.020, P = 0.189), or non-ischemic cardiomyopathy (random-effect IVW, OR per SD increase in homocysteine levels = 1.064, 95% CI = 0.927–1.222, P = 0.379). The results were consistent with other analytical methods and sensitivity analyses. Conclusion Genetically predicted homocysteine level was not associated with congestive heart failure or cardiomyopathy risk. It is unlikely that homocysteine-lowering therapy decreases the incidence or improves the outcomes of congestive heart failure and cardiomyopathy.